Clinical efficacy of treatment for subclinical-stage axial diabetic optic neuropathy - M.A. Karliychuk; P.A. Bezditko (Ukrainian Society of Ophthalmologists, 2018)
Background: There is no standard of therapy for the treatment of diabetic optic neuropathy (DON). Purpose: To assess the clinical efficacy of thioctic acid, topical brimonidine tartrate and a combination of vitamins В1, В6, and В12 in the management of subclinical-stage axial DON. Materials and Methods: Forty patients (63 eyes) were followed up after being diagnosed with subclinical-stage axial DON. The adjunct group was composed of 20 patients (32 eyes) who were administered (1) thioctic acid (Berlithion) at a dose of one 300 mg tablet a day for 42 days, (2) a 2 ml intramuscular injection of Milgamma, once per 3 days for 21 days, followed by switching to oral regimen, 1 tablet per 3 days for 21 days in two courses during a year, and (3) topical brimonidine tartrate 0.2%, 1-2 drops twice a day on a constant basis, as adjunctive to hypoglycemic therapy. The control group (20 patients; 31 eyes) received hypoglycemic therapy only. In addition to routine eye examination, retinal and optic nerve optical coherence tomography and electrophysiology were performed. Patients underwent an examination at baseline, 1.5 months, 6 months, 7.5 months, 13.5 months, 24 months and 25.5 months after treatment. Results: No progression of optic nerve damage was found in all 32 affected eyes of the adjunct group versus no progression, progression to mild-stage axial DON, and progression to advanced-stage axial DON in 64.5% (20 eyes), 35.5% (11 eyes) and 6.5% (2 eyes), respectively, of the controls at the 25.5-month time point. We found that our treatment attenuated the progression of optic nerve damage in subclinical-stage axial DON, with 25.9% better visual acuity, 29.5 % lower electrically evoked phosphene thresholds, 69.3% less ganglion cell complex (GCC) focal loss volume (FLV), and 29.8% less thickness of the cribriform plate compared to controls at 25.5 months. Conclusion: Our treatment was found to be clinically efficacious in attenuating the progression of optic nerve damage in subclinical-stage axial DON.